A Holistic and Globally Applicable Indication System for Regional Electric-Energy-Water Security - Tobias Landwehr (Taylor & Francis Group, 2021)
The seventeen Sustainable Development Goals (SDGs) were designed to lead the modern Anthropocene to a lifestyle that was demanded by the Brundtland commission. Their objective is a common good that does not exploit the planet’s environment and is thus long-term. Though virtually separated, contemporary research shows that the seventeen SDGs are in- tertwined. This is also the case for water and energy (SDG 6 and 7). The present research offers the first holistic indicator set that is designed to demonstrate the synergies and trade-offs between electrical energy gener- ation and necessary water supply. It is founded on the SDG principles, follows a mindset based on the security definition established by Grey and Sadoff and is designed around the various technical dependencies of electrical energy and water. The set endeavors to reflect the manifoldness by which electrical energy is dependent on water supply in a dynamic eco- logic, economic and social environment. As electrical energy and water interactions are identified for a regional level, the set is designed to be applicable on any administrative or basin area with moderate data avail- ability. Thereby, the set includes industrializing and non-industrialized countries. It is based on six main indicators and sixteen sub indicators and seen as conceptual design for further discussion before application. The present paper argues and presents how those indicators are formed, why they are need, how and why they should be applied and why it is necessary if not inevitable to design cross-SDG indicators in a holistic view.